PENGEMBANGAN DESAIN DIDAKTIS UNTUK MENGATASI LEARNING OBSTACLE PADA MATERI DIMENSI TIGA - Nelly Fitriani; Gida Kadarisma; Risma Amelia (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
This research is motivated by the many learning obstacles experienced by students in understanding the three-dimensional material, while the teaching materials used by teachers are inadequate because they do not pay attention to student needs. Therefore, this study aims to determine the characteristics of Learning obstacles that occur in students in the three dimensional material as well as to find out the didactic designs used in overcoming Learning obstacles. Didactic design developed in the form of teaching materials are arranged based on four things, namely learning obstacle that occurs, learning trajectory, didactical situation theory and the process of abstraction. The research method used is a qualitative method with a didactic design approach. The subjects in this study were 35 students of class X SMAN 4 Cimahi, with instruments in the form of Respondents' Ability Tests about 5 questions and validation sheets of teaching materials from expert validators. The results showed that the characteristics of Learning obstacle that occurred in the three dimensional material were Ontogenic Obstacle, Didactical Obstacle and Obstacle Epistemology. Then a didactic design was made which was implemented as many as 6 meetings with a validation percentage of 69.5% expert validator, a retrospective analysis was carried out to analyze the students' responses to the didactic hypothesis design, because there were still mismatches of student responses and obstacle epistemology was still found. the validation percentage increased to 76% with a valid category. Based on the implementation, this didactic design can overcome the learning obstacles experienced by students in the three dimensional material. The implications of this study, the good teaching materials provided to students must be arranged based on the needs of students which, including analysis of learning obstacles and student learning trajectories so that learning objectives can be achieved.